Las gated communities como expresión de los nuevos contextos urbanos y socioculturales: un estado de la cuestión - Prada Trigo, José (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2010)
This paper analyzes the phenomenon of gated communities from different perspectives. Firstly it develops a background to the origin and definition of the concept, highlighting the multiple ways to calling these gated residential areas. Next, a general interpretation about the rise of gated communities in contemporary society is developed as a result of three global processes: the social and cultural context of the Postmodernity, the fragmentation and specialization of urban space and the increased fears and insecurities in citizens. After it, the rise in importance and extent of the gated communities’ phenomenon throughout the world is showed. The article concludes by a briefly explaining of how this phenomenon has been reflected in literature and cinema, through several examples.